Towards a utility based computational model for negotiation between semantic Web services - Kumar S.; Mastorakis N.E. (My University, 2025)
Using the utility-theory for the decision-making process during the negotiation between semantic web services is an appealing one. This paper proposes a computational model for the calculation of utilities of the negotiating semantic web services. The proposed model uses multiple attribute in the utility function and uses the basic values of these attributes such as values for offered price, quality and others. The model is based on a novel understanding that a service requester should remain indifferent to the changes in price or other such values if the corresponding quality has also been changed accordingly. A prototype system has been implemented in support of the proposed model. The work has been evaluated and the betterment has been reported.